Aspects techniques de l’ordinateur - Labelle, Pierre; Laurendeau, Jean-Claude (Assurances)

(untitled) (HEC Montréal, 1981)
Messrs. Pierre Labelle and Jean-Claude Laurendeau have attempted, inasmuch as it was possible, to interpret in the simplest and least technical manner the functioning of a computer system. Their study is not intended for experts. Rather, it is aimed at the layman interested in knowing what a computer is, how it works, the quality of information it can produce and whether the system has been conceptualized and adapted to meet the needs of the user.